Strengthening n Integrated Participatory Commitment in the Organization of Archives for Village Heads in the Pemalang District - Agung Kuswantoro; Arif Wahyu Wirawan; Muhamad Nukha Murtadloc; Dedi Kurniawan (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community service aims to increase integrated participatory commitment in archival management for village heads throughout Pemalang District. Good archive management will encourage the creation of Good Governance. Effective archive management is an essential pillar in transparent and accountable village governance. This activity involves village heads in training activities, workshops and technical guidance designed to strengthen their capacity in managing archives. The methods include outreach, workshops, and direct guidance in implementing an effective archiving system. The service results show an increase in the technical abilities and commitment of village heads in organizing archives, as well as an increase in awareness of the importance of good archives. It is hoped that strengthening this participatory commitment will have a positive impact on archive management in Pemalang District villages, which will ultimately support improving the quality of public services and village governance. In administering archives, it is not enough to have archives policies, archives infrastructure, competence of archivists/archivists, and archives funding. However, there also needs to be integrated participatory commitment. Participatory commitment is an integrated concept of the three participatory commitments (normative, sustainable, and affective) in every component in archival administration.